1980
DOI: 10.1063/1.438935
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of resolution of proton chemical shifts in solids: Combined multiple pulse NMR and magic-angle spinning

Abstract: High-resolution nuclear magnetic resonance spectra of protons in rigid, randomly oriented solids have been measured using combined homonuclear dipolar decoupling (via multiple pulse techniques) and attenuation of chemical shift anisotropies (via magic-angle sample spinning). Under those conditions, isotropic proton chemical shifts were recorded for a variety of chemical species, with individual linewidths varying from about 55 to 110 Hz (1–2 ppm). Residual line broadening was due predominately to (i) magnetic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Proton MAS spectra obtained at high spinning rates and high fields exhibit significant line narrowing (1). The combination of multiple-pulse NMR and MAS can result in high-resolution spectra (2) and in recent publications this approach has been extended and improved (3). The frequency-switched Lee-Goldburg (4) has provided an alternative approach for detecting high-resolution spectra and lately it has been implemented in two-dimensional MAS experiments (5).…”
Section: Introductionmentioning
confidence: 99%
“…Proton MAS spectra obtained at high spinning rates and high fields exhibit significant line narrowing (1). The combination of multiple-pulse NMR and MAS can result in high-resolution spectra (2) and in recent publications this approach has been extended and improved (3). The frequency-switched Lee-Goldburg (4) has provided an alternative approach for detecting high-resolution spectra and lately it has been implemented in two-dimensional MAS experiments (5).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method is perhaps the 8-pulse MREV-8 sequence (4,5). The combination of magic angle spinning and multiplepulse dipolar decoupling (CRAMPS,(15)(16)(17) has proven to be very useful in obtaining high-resolution proton spectra of solids. In 1989, Levitt and co-workers (11,12) demonstrated that the "magic-angle CW" method of Lee and Goldburg (1) can be dramatically improved by frequency switching.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown quences (6)(7)(8). Subsequently, Gerstein et al (9) confirmed that substantial narrowing of the proton linewidths of organic that single-pulse excitation with acquisition delay or spin solids can be achieved by using single-pulse excitation with acquisi-echo allows the observation of narrow peaks, and suggested tion delay or spin echo [S. Ding and C. A. McDowell, J. Magn.…”
mentioning
confidence: 99%